Transformation of Agricultural Waste into Silica–Cellulose Microsponge Adsorbent for Optimization of Waste Cooking Oil as Biodiesel Feedstock - Sipayung, Rosmawati; Rahma Amalia; Rara Ayu Lestary; Nita Widyastuti; Oki Alfernando; Ira Galih Prabasari; Nazarudin; Putri Ananda; Intan Nandia Sakti (Program Studi Teknik Kimia, Universitas Pamulang, 2026)
The utilization of used cooking oil as a biodiesel feedstock is hindered by its high free fatty acid (FFA) content, which interferes with the transesterification process. This study aims to reduce FFA levels through adsorption using a silica–cellulose-based microsponge adsorbent synthesized from rice husk ash and corn cob waste. The investigated process variables include adsorbent mass (1, 3, 5 g), temperature (30, 45, 60 °C), contact time (30, 60, 90 minutes), and silica-to-cellulose ratios (40:60, 50:50, 60:40). FTIR analysis revealed characteristic peaks of Si–O–Si ( 1053 cm⁻¹) and Si–O ( 795 cm⁻¹) indicating the presence of amorphous silica, while the O–H stretching ( 3200–3500 cm⁻¹) of cellulose appeared weaker due to silica dominance on the surface. This confirms the successful formation of the silica–cellulose composite with strong chemical interaction. Furthermore, Brunauer–Emmett–Teller (BET) analysis showed a specific surface area of 87.77 m²/g with mesoporous characteristics, confirming the microsponge structure with high affinity toward polar molecules such as FFA. The optimum conditions were obtained at 5 g adsorbent mass, 30 °C, 60 minutes contact time, and a 60:40 silica-to-cellulose ratio, achieving an FFA reduction efficiency of 49.62%. These physicochemical properties make the adsorbent efficient, energy-saving, and environmentally friendly, highlighting the great potential of agricultural waste transformation into active materials for pre-purification of used cooking oil toward sustainable biodiesel production.